Immunosenescence: A Critical Factor Associated With Organ Injury After Sepsis - Lu, Xuan; Yang, Yun-Mei; Lu, Yuan-Qiang (Frontiers in Immunology, 2022)
Progressive immune dysfunction associated with aging is known as immunosenescence. The age-related deterioration of immune function is accompanied by chronic inflammation and microenvironment changes. Immunosenescence can affect both innate and acquired immunity. Sepsis is a systemic inflammatory response that affects parenchymal organs, such as the respiratory system, cardiovascular system, liver, urinary system, and central nervous system, according to the sequential organ failure assessment (SOFA). The initial immune response is characterized by an excess release of inflammatory factors, followed by persistent immune paralysis. Moreover, immunosenescence was found to complement the severity of the immune disorder following sepsis. Furthermore, the immune characteristics associated with sepsis include lymphocytopenia, thymus degeneration, and immunosuppressive cell proliferation, which are very similar to the characteristics of immunosenescence. Therefore, an in-depth understanding of immunosenescence after sepsis and its subsequent effects on the organs may contribute to the development of promising therapeutic strategies. This paper focuses on the characteristics of immunosenescence after sepsis and rigorously analyzes the possible underlying mechanism of action. Based on several recent studies, we summarized the relationship between immunosenescence and sepsis-related organs. We believe that the association between immunosenescence and parenchymal organs might be able to explain the delayed consequences associated with sepsis.